Revitalization of traditional games through floor murals: integrating visual arts and culture in schools - Ridha, Sahbana; Warni, Herita; Arifin, Syamsul (Department of Coaching, Faculty of Sports Science, Universitas Negeri Padang, Indonesia, 2025)
Problems: Traditional games are an essential part of Indonesia's cultural heritage, providing educational, social, and physical benefits. However, the rapid advancement of digital technology and changing lifestyles have led to a decline in children's engagement with these games, reducing opportunities for physical activity and social interaction. Purpose: To address this issue, this study explores the integration of traditional games into floor murals as an innovative approach to revitalizing cultural heritage in school environments. Methods: Using a literature review method, this research analyzes relevant sources, including academic journals, books, and previous studies, to examine the role of murals in cultural preservation and education. Results: The findings suggest that floor murals depicting traditional games serve not only as artistic decorations but also as interactive learning media. These murals encourage students to engage in physical activities, enhance their social interactions, and develop a deeper appreciation for local culture. Additionally, integrating traditional games into murals helps reduce children's dependency on digital devices while promoting a healthier and more active lifestyle. Moreover, floor murals provide a creative and immersive educational experience, allowing students to learn through play. They contribute to cognitive and motor development by encouraging strategic thinking, teamwork, and rule comprehension. However, challenges such as material durability, mural maintenance, and the role of educators in facilitating student engagement need to be carefully considered to ensure long-term effectiveness. Collaboration between schools, local communities, and artists is essential to sustain the impact of this initiative. Conclusion: This study highlights the importance of incorporating cultural heritage into educational settings through innovative methods. Floor murals can serve as a sustainable solution for preserving traditional games, enriching the school environment, and fostering a strong cultural identity among students.